EFFECT OF GINGER RHIZOME (ZINGIBER OFFICINALE) METHANOLIC EXTRACT ON SOME OXIDATIVE STRESS MARKERS IN ALLOXAN-INDUCED DIABETIC RATS - GADANYA A.M; SAIFULLAHI B.; ABUBAKAR S.M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The prevalence of diabetes mellitus is rising all over the world. Much evidence suggests major role of reactive oxygen species/oxidative stress in development and progression of diabetic complications. In the current study, the antioxidant potentials of methanolic extract of ginger rhizome (Zingeber officinale) in alloxan-induced diabetic rats were evaluated. Thirty (36) healthy albino rats were randomly divided into six groups of six rats each: positive control group (PC), normal control group (NC), metformin control group (MC) and experimental groups i.e Groups 1, 2, and 3 which were orally administered with methanolic extract of ginger rhizome on daily doses of 1500mg/Kg, 1000mg/Kg and 500mg/kg body weight respectively for six weeks. Results of the study showed significant (p<0.05) increase in serum levels of reduced glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) activities of GR1 (9.0±1.3 μmol SOD/min/mg of protein), (28.3±2.2 mg/dl) and (31.4±3.1 IU/l) respectively, GR2 (8.6±2.4 μmolSOD/min/mg of protein), (25.1±3.2 mg/dl), and (31.1±3.9 IU/l) respectively, and GR3 (8.2±2.3 μmolSOD/min/mg of protein), (24.7±4.0 mg/dl) and (28.1±2.2 IU/l) respectively when compared with that of positive control group (4.2±0.5 μmolSOD/min/mg of protein), (19.4±2.3 mg/dl), and (22.9±2.1 IU/l) respectively. A significant (p<0.05) decrease was found in the level of malondealdehyde (MDA) in GR1, GR2, and GR3 (54.8±5.2 nmol/L, 65.3±5.5 nmol/L, and 72.9±4.3 nmol/L respectively) when compared with that of positive control group (101.8±8.7 nmol/l). Thus, ginger has the potentials to lower the effect of oxidative stress in alloxan-induced diabetic rats.